2000
DOI: 10.1200/jco.2000.18.13.2505
|View full text |Cite
|
Sign up to set email alerts
|

Complementary/Alternative Medicine Use in a Comprehensive Cancer Center and the Implications for Oncology

Abstract: In most categories, CAM use was common among outpatients. Given the number of patients combining vitamins and herbs with conventional treatments, the oncology community must improve patient-provider communication, offer reliable information to patients, and initiate research to determine possible drug-herb-vitamin interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

57
686
20
26

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 909 publications
(789 citation statements)
references
References 50 publications
57
686
20
26
Order By: Relevance
“…In contrast to earlier research about gender differences in CAMuse (Molassiotis et al, 2005;Richardson et al, 2000), no differences in CAM-use among women and men were found in this study. One possible reason for these contradictory research results might be related to the group studied as well as differences in how men and women respond to symptoms.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to earlier research about gender differences in CAMuse (Molassiotis et al, 2005;Richardson et al, 2000), no differences in CAM-use among women and men were found in this study. One possible reason for these contradictory research results might be related to the group studied as well as differences in how men and women respond to symptoms.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite the link between dissatisfaction with care and increased use of CAM, few studies have explored LC-patients use of CAM. While it is known that cancer patients report using more CAM than the general population (Mao et al, 2007), the prevalence varies from 7e83% in different studies (Ernst and Cassileth, 1998;Richardson et al, 2000). The only relevant European study found that approximately one quarter of LC-patients in eight European countries including Sweden, used CAM (Molassiotis et al, 2006).…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…More recent studies have reported an even higher prevalence of between 70 and 80% (Richardson et al, 2000;Bernstein and Grasso, 2001;Ashikaga et al, 2002). The nature of CAMs used, for example, vitamins and other supplements, herbal remedies, physical and psychological treatments, also varies greatly (Risberg et al, 1998;Richardson et al, 2000;Sparber et al, 2000;Bernstein and Grasso, 2001;Ashikaga et al, 2002).…”
mentioning
confidence: 99%
“…Around 40 % of cancer patients in Germany use CAM during or after cancer treatment [7]. Since the 1970s, the percentages of cancer patients in western industrialized nations using CAM has continually risen, from 25 to 49 % [7][8][9][10]. In the USA, Australia and Europe between 38 and 60 % of all cancer patients use CAM during the course of disease for therapeutic support [1,11,12].…”
mentioning
confidence: 99%